Composition, thickness and properties of grafted copolymer brush coatings determined by ellipsometry: calculation and prediction. Issue 6 (12th January 2018) - Kostruba, Andriy; Stetsyshyn, Yurij; Mayevska, Sofija; Yakovlev, Maksym; Vankevych, Petro; Nastishin, Yuriy; Kravets, Vasyl
Abstract : Predicted changes in comparison with the experimental data for the refractive index and thickness of [P(4VP- co -OEGMA246)] copolymer grafted brush coatings. Abstract : The composition, thickness and properties of poly(4-vinylpyridine- co -oligo(ethylene glycol)ethyl ether methacrylate246) [P(4VP- co -OEGMA246)] copolymer grafted brush coatings attached to glass were studied in the dry and swollen states using ellipsometry. These measured data are in good agreement with predicted (estimated) changes in the amount of water, refractive index and thickness of the grafted copolymer brush coatings on swelling. For POEGMA brushes the thickness of the coatings on swelling at 20 °C can be more than double, in contrast to P4VP where those changes are insignificant. The presence of 4VP units in the structure of the P(4VP- co -OEGMA246) copolymer grafted brushes significantly decreases the hydration degree even for coatings with very low concentrations of 4VP units.